ANALISIS KELAYAKAN VIDEO PEMBELAJARAN UNTUK JENJANG SD DI SALURAN YOUTUBE RUANGGURU DAN LABEDU CHANNEL - Cahyana, Ari Dwi; Kosasih, Ekos (IKIP Siliwangi, 2021)
AbstractThis descriptive study uses an analytical method that aims to analyze learning videos for elementary school on the Ruangguru youtube channel with Labedu Channel. The analysis included content analysis, presentation analysis, language analysis, and graphical analysis. Researchers analyzed five learning videos on Ruangguru channel and Labedu Channel. The aspects of the feasibility of the contents are all categorized as very feasible, the feasibility aspects of the presentation of all are categorized as very feasible, the aspects of feasibility of the language are three learning videos categorized as very feasible and two learning videos are each categorized as feasible and quite feasible, for the graphic feasibility aspects four learning videos are categorized as very feasible and one Learning videos are categorized as feasible. Then the results of the analysis on the Labedu Channel are summarized all aspects of content eligibility are categorized as very feasible, aspects of presenting four videos are categorized as very feasible and one video is categorized as feasible, aspects of language there are four videos categorized as very feasible and one video is categorized as feasible and finally the graphic aspect there are two videos categorized as very feasible and the other two are categorized as feasible. Keywords : Descriptive analysis, learning video, content analysis AbstrakPenelitian deskriptif ini menggunakan metode analisis yang bertujuan untuk menganalisis video pembelajaran untuk jenjang SD pada saluran youtube Ruangguru dengan Labedu Channel. Analisis yang dilakukan diantaranya analisis isi, analisis penyajian, analisis bahasa, dan analisis grafika. Peneliti menganalisis lima video pembelajaran pada saluran Ruangguru dan Labedu Channel. Aspek kelayakan isi semua dikategorikan sangat layak, aspek kelayakan penyajian semua dikategorikan sangat layak, aspek kelayakan bahasa tiga video pembelajaran dikategorikan sangat layak dan dua video pembelajaran masing-masing dikategorikan layak dan cukup layak, untuk aspek kelayakan grafika empat video pembelajaran dikategorikan sangat layak dan satu video pembelajaran dikategorikan layak. Kemudian hasil analisis di saluran Labedu channel meliputi aspek kelayakan isi semua dikategorikan sangat layak, aspek penyajian empat video dikategorikan sangat layak dan satu video dikategorikan layak, aspek bahasa terdapat empat video dikategorikan sangat layak dan satu video dikategorikan layak dan terakhir aspek grafika terdapat dua video dikategorikan sangat layak dan dua lainnya dikategorikan layak. Kata Kunci: Analisis deskriptif, video pembelajaran, analisis isi